Weeds Growth in Various Population of Sweet Corn+Peanut Intercropping - Dwi Ndaru Sekar Asih; Agus Nugroho Setiawan; Sarjiyah Sarjiyah (Universitas Muhammadiyah Yogyakarta, 2018)
The existence of weeds on sweet corn crops can lead to competition that reduce the yield. The aim of this research was to obtain the optimum crop proportion of corn-peanut plants in suppressing weed growth but not decrease the yield of sweet corn. The experiment was conducted using a single factor field experimental method arranged in a complete randomized block design with 3 blocks as replication. The treatment was the proportion of sweet corn-peanut population consisting of 3 levels, i.e 1:1, 1:2, 1:3, sweet corn monoculture and peanut monoculture as comparison.The results of this research showed that intercropping of sweet corn+peanut with population proportion of 1:2 can suppress weed growth in on the 9th week (at harvest) without decreasing sweet corn yield.